Helen Cintiyawati, Ikhsanudin, Sofian English Education Study Program, Language and Arts Education Department, Teacher Training and Education Faculty of Tanjungpura University Pontianak Email : helen.cintiyawati@gmail.com - Cintiyawati, Helen; ., Ikhsanudin; ., Sofian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research was conducted to investigate the students’ needs for learning procedure text, to design origami task that will be used for teaching procedure text, and to evaluate whether or not the model origami tasks are feasible for teaching procedure text. This research involved an English teacher and 33 seventh grade students of class A in SMP Negeri 11 Pontianak. The method of this research is development research which consists of five phases. They are analyze, design, develop, implement and evaluate or called ADDIE. The need analysis in this research obtained the following information about what students need in learning procedure text by identifying the analysis of students’ condition, the analysis of teacher’s perspectives, the analysis of the textbook, and the analysis of learning procedure text through origami. The origami tasks were suitable for teaching procedure text for seventh grade students because origami tasks were interesting, understandable, easy to find, and cost efficient for them in learning procedure text. The result of task evaluation showed that the origami tasks were feasible for teaching procedure text. Keywords: Origami, Procedure Text, Development Research Abstrak: Penelitian ini dilaksanakan untuk mengetahui apa yang dibutuhkan siswa dalam belajar teks prosedur, untuk mendesain tugas berbasis origami yang akan digunakan dalam pengajaran teks prosedur, dan untuk mengevaluasi apakah tugas berbasis origami dapat digunakan dalam pengajaran teks prosedur atau tidak. Penelitian ini melibatkan guru bahasa Inggris dan 33 siswa kelas A di SMP Negeri 11 Pontianak. Metode yang digunakan dalam penelitian ini adalah penelitian pengembangan yang terdiri dari lima fase, yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Analisis dalam penelitian ini mengandung beberapa informasi terkait kebutuhan siswa dalam belajar teks prosedur dengan menganalisis kondisi siswa, perspektif guru, buku teks pelajaran, dan belajar teks prosedur melalui origami. Tugas berbasis origami yang dibuat cocok untuk pengajaran teks prosedur untuk siswa kelas tujuh karena tugas berbasis origami tersebut menarik bagi siswa, mudah dipahami, mudah didapat, dan hemat biaya dalam belajar teks prosedur. Hasil dari evaluasi tugas berbasis origami menunjukkan bahwa tugas berbasis origami tersebut dapat digunakan dalam pengajaran teks prosedur. Kata Kunci: Origami, Teks Prosedur, Penelitian Pengembangan